2020
DOI: 10.1109/access.2020.2985345
|View full text |Cite
|
Sign up to set email alerts
|

On the Design of Logarithmic Multiplier Using Radix-4 Booth Encoding

Abstract: This paper proposes an energy-efficient approximate multiplier which combines radix-4 Booth encoding and logarithmic product approximation. Additionally, a datapath pruning technique is proposed and studied to reduce the hardware complexity of the multiplier. Various experiments were conducted to evaluate the multiplier's error performance and efficiency in terms of energy and area utilization. The reported results are based on simulations using TSMC-180nm. Also, the applicability of the proposed multiplier is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 46 publications
(81 reference statements)
1
22
0
Order By: Relevance
“…Multiplication represents a widespread arithmetic operation in DSP; therefore, many DSP applications can benefit from an efficient multiplier design. By relaxing the requirement for exact computation, we can design a power-efficient approximate multiplier [ 11 , 12 , 13 , 14 , 15 ]. The error that emerges from product approximation should be constrained to deliver acceptable results in the application.…”
Section: Introductionmentioning
confidence: 99%
“…Multiplication represents a widespread arithmetic operation in DSP; therefore, many DSP applications can benefit from an efficient multiplier design. By relaxing the requirement for exact computation, we can design a power-efficient approximate multiplier [ 11 , 12 , 13 , 14 , 15 ]. The error that emerges from product approximation should be constrained to deliver acceptable results in the application.…”
Section: Introductionmentioning
confidence: 99%
“…Multiplication is a very common, but expensive operation, with exact multipliers being large circuits that consume a significant amount of energy. Various approximate multipliers have been proposed in recent years [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Many studies reported that approximate multipliers behave well in neural network processing [ 56 , 59 , 60 , 61 , 63 , 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the approximate multiplier design, we balanced accuracy and energy efficiency to suit the application’s needs. Various approximate multipliers have been proposed in recent years [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Approximate multipliers follow one of three design strategies: the approximate logarithmic design, the approximate nonlogarithmic design, and the hybrid design.…”
Section: Introductionmentioning
confidence: 99%
“…Multipliers are one the most power‐hungry units, which directly influence the overall performance of the computing systems. Therefore, utilizing approximate computing methods can significantly improve the performance of the multipliers regarding power consumption, speed, and transistor count 15‐17 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, utilizing approximate computing methods can significantly improve the performance of the multipliers regarding power consumption, speed, and transistor count. [15][16][17] Typically, multiplication is commenced by generating partial products with an array of AND gates. This process is followed by the reduction of the partial products and then the final summation for computing the final results.…”
Section: Introductionmentioning
confidence: 99%